Development Of Warehouse Pest Sitophilus zeamais Motsch. On Corn Seed Varieties Bisi 18, Jh 37, Lamuru, Pertiwi 3 And Batras 1 In The Laboratory - Tambelu, Merry Feiby; Tarore, Dantje; Rimbing, Jimmy; Paat, Frangky J. (Jurnal Agroekoteknologi Terapan, 2024)
Seeds are an important input for increasing corn production and productivity. The use of low-quality seeds causes low corn production. The research aims to determine the development of the S. zeamais pest on corn seeds of varieties Bisi 18, JH 37, Lamuru, Pertiwi 3, and Batras 1. This research used a Completely Randomized (CRD) design with five treatments and three replications. As treatments were 5 varieties of corn seeds, namely Bisi 18, JH 37, Lamuru, Pertiwi 3, and Batras 1. The research method used was the Experimental Method, namely experimental research by researching the influence of the S. zeamais pest on five varieties of corn seeds. The results of variance analysis of differences in S. zeamais populations on corn seeds of the Bisi 18, Jh 37, Pertiwi 3, and Batras 1 varieties showed that the results were not significantly different except for the Lamuru variety which had significant differences. These data show that the Lamuru variety has the highest population of the S. zeamais pest. The high population of the pest S. zeamais on corn seeds of the Lamuru variety compared to other varieties could be caused by the pest being more attracted to the physical condition, nutritional, and chemical content of the seeds. The results of variance analysis of differences in damage between corn seed varieties due to S. zeamais attack showed real and very significant differences, except between the Betras 1 and Pertiwi 3 varieties which were not significantly different. The Lamuru variety has a higher number of damaged or hollow corn seeds compared to other varieties. Differences in the nutrient content and seed hardness of each corn seed variety can cause high damage to the Lamuru variety. Keywords: Warehouse Pests, Sitophilus oryzae, Experimental methods, Pest populations, damage to corn seeds. Abstrak Benih merupakan input penting bagi peningkatan produksi dan produktivitas tanaman jagung. Penggunaan benih dengan mutu rendah menyebabkan produksi jagung rendah. Penelitian bertujuan mengetahui perkembangan hama S. zeamais pada benih jagung varietas Bisi 18, JH 37, Lamuru, Pertiwi 3 dan Batras 1. Penelitian ini menggunakan rancangan Acak Lengkap (RAL) dengan lima perlakuan dan tiga ulangan. Sebagai perlakuan adalah 5 varietas benih jagung yaitu Bisi 18, JH 37, Lamuru, Pertiwi 3 dan Batras 1. Metode penelitian yang digunakan adalah Metode Eksperimen (Experimental Method) yaitu penelitian percobaan dengan melakukan penelitian pengaruh hama S. zeamais pada lima varietas benih jagung. Hasil analisa varians perbedaan populasi S. zeamais pada benih jagung varietas Bisi 18, Jh 37, Pertiwi 3 dan Batras 1 menunjukkan hasil yang tidak berbeda nyata kecuali terhadap varietas Lamuru memiliki perbedaan nyata. Data tersebut menunjukkan bahwa varietas Lamuru memiliki populasi hama S. zeamais tertinggi. Tingginya populasi hama S. zeamais pada benih jagung varietas Lamuru dibandingkan dengan varietas yang lain dapat disebabkan karena hama tersebut lebih tertarik pada keadaan fisik, kandungan nutrisi dan kimia biji benih tersebut. Hasil analisa varians perbedaan kerurasakan antar varietas benih jagung akibat serangan S. zeamais menunjukkan adanya perbedaan yang nyata dan sangat nyata, kecuali antara varietas Betras 1 dan pertiwi 3 tidak berbeda nyata. Varietas Lamuru memiliki jumlah biji benih jagung rusak atau berlubang dibandingkan dengan varietas lain. Tingginya kerusakan pada varietas Lamuru dapat disebabkan karena adanya pembedaan kandungan gisi dan kekerasan biji pada setiap varietas benih jagung. Kata kunci: Hama Gudang, Sitophilus oryzae,Mitode eksperimen, Populasi hama, kerusakan benih jagung